Modulatory effects of verapamil in rifampicin activity against Mycobacterium tuberculosis - Caleffi-Ferracioli, Katiany R.; Cardoso, Rosilene F.; Souza, Joao V. P. de; Murase, Leticia S.; Canezin, Pedro H.; Scodro, Regiane B. L.; Siqueira, Vera L. D.; Pavan, Fernando R. [UNESP] (Future Medicine Ltd, 2019)
Aim: To evaluate modulatory effect of verapamil (VP) in rifampicin (RIF) activity and its effect in efflux pumps (EPs) transcript levels in Mycobacterium tuberculosis. Materials & methods: RIF and VP minimal inhibitory concentration, combinatory effect and detection of mutations were determined in 16 isolates. EPs transcript levels were determined in four isolates by real-time PCR after exposure to drugs. Results: VP showed good combinatory effect among RIF-resistant isolates. This effect was also observed in the relative transcript levels of EPs, mainly after 72h of exposure, depending on the EP gene, genotype and the resistance profile of the isolate. Conclusion: Additional regulatory mechanisms in the EP activities, as well as, interactions with other drug-specific resistance mechanisms need further investigation in M. tuberculosis.
Keywords: efflux pump inhibitor; gene regulation; multidrug transporters; Mycobacterium tuberculosis; real-time PCR; resistance; rifampicin; synergism; tuberculosis; verapamil